Optimization of the Combination Between Glucomannan Flour from Porang Tuber and Hunkue Flour in View of Chemical and Organoleptic Characteristics of Cookie - Susanti, Siti (Communication in Food Science and Technology, 2023)
This study aims to determine the optimal combination of hunkue flour and porang tuber glucomannan flour to manufacture cookie. The materials used are porang tuber glucomannan flour, hunkue flour, and ingredients for making cookie. The experimental design was completely randomized design with 5 treatments and 4 replications. The treatment was a combination of the ratio of porang tuber glucomannan flour and hunkue flour. The treatment given was T1 = 0% Glucomannan Flour: 100% Hunkue Flour, T2 = 20% Glucomannan Flour: 80% Hunkue Flour, T3 = 40% Glucomannan Flour: 60% Hunkue Flour, T4 = 60% Glucomannan Flour: 40% Flour Hunkue, and T5 = 80% Glucomannan Flour: 20% Hunkue Flour. The data analysis used was Analysis of Variance (ANOVA) at a significance level of 5%. The results showed that the combination ratio of porang tuber glucomannan flour and hunkue flour had a significant effect (p<0.05) on moisture content, protein, fat, ash, carbohydrates, texture, taste, and preferences of cookie, but did not have a significant effect on crude fiber content, color, and aroma. Treatment with a ratio of glucomannan flour of 20% was the best treatment for organoleptic parameters as a whole.